The mechanics of a compressive sand mixed with tyre rubber. Issue 3 (14th July 2014) - Li, X. Q.; Fu, R.; Coop, M. R.
Abstract : The effects of the addition of waste tyre products have been extensively investigated in dilative quartz sands, but little is known about their effect on the behaviour of compressive, crushable sands. Rubber granules and fibres were introduced into a decomposed granite in two different proportions, 10 and 30% by weight. It was found that a critical state framework could be successfully applied to the behaviour of the mixtures and that a 30% fibre content gave a significant strength increase, whereas a 10% fibre content and both 10 and 30% granules did not. The paper examines the interacting effects of the rubber and particle breakage in causing volume change. Although the change to the compression index through the addition of rubber was not large, the overall compressibility does increase significantly as a result of increased compression before the normal compression line is reached, giving a downward movement of the line. Similarly the most significant change to the critical state line location in the specific volume–log mean stress plane was a shift downwards with increasing rubber content.